THE INFLUENCE OF PRODUCT QUALITY AND BRAND IMAGE ON CUSTOMER LOYALTY HAMMERSTOUT DENIM CLOTHING - et. al., Mariana Rachmawati, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Economic development will greatly affect the progress of a country. One of them in the textile industry, talking textile does not escape the name of fashion, fashion development also will affect the consistency of a brand. Having a good brand quality and image will not guarantee consumers' loyalty to the product. Factors in this study aim to determine the effect of product quality and brand image on customer loyalty at Hammerstout Denim Clothing. This study uses descriptive and verification research methods. The sample of this study was consumers who bought 95 products of Hammerstout Denim Clothing with Nonprobability sampling sampling technique. Data collection uses questionnaires that have been tested for validity and reliability. Data analysis techniques were carried out using multiple regression analysis. The results showed that product quality and brand image had a positive and significant effect on customer loyalty on Hammerstout Denim products. It is known that the calculated f value is 16,032. Based on the regression test, R square is 25.80%, which means that the Product Quality and Brand Image has an effect of 25.80% on Customer Loyalty, while the remaining 74.20% is influenced by other variables not discussed in this study